NICE guidance for off-pump CABG: keep the pump primed. Issue 21 (2nd September 2011) - Pepper, John R
Abstract : Because of a desire to reduce the morbidity of a well-established and effective procedure for coronary artery disease, up to 30% of coronary bypass operations are being performed without the use of a heart–lung pump. Concerns remain about the quality of the coronary anastomoses and the completeness of revascularisation. Randomised trials have not disclosed the significant reduction in morbidity or mortality that the early enthusiasts had hoped for. Yet a number of non-randomised studies have shown clinical benefit with the avoidance of an extracorporeal circulation, but these studies have been criticised for potential bias in patient selection and management. Most surgeons have not yet adopted this technique and are waiting for more evidence.